Coronavírus canino: fatores limitantes de padronização para multiplicação em linhagens celulares e ensaio sorológico - Sergio Luiz de Freitas Balsamao (1994)
There were studied three continual cells lines (CRFK, MDCK and A-72), for the purpose of nutritional requirements and development and also for sensitivity to the canine coronavirus (CCV). The best conditions for A-72 line were done using the L-15 GIBCO media with 10% of fetal bovine sera (FCS) on initial concentrations of 3,0 to 4,0 x 10 4 cells/cm' in disposable plastic bottles with weekly sub-culture and change of the medium with 5% of FCS each two days of incubation. Initial concentrations of 7,0 to 8,0 x 10 4 cells/cm' in L-15 with 5% FCS at 37°C without the CO2 atmosphere were excellent for the microplates cultures. It was the most sensitive to the CCV, obtainning good titers in less time,10 5 10 6 DICC50/25uL however the most difficult and unstable, V being used for the initial activation and isolations. For the CRFK and MDCK lines the best conditions were a using the MEM-EAGLE with non essential aminoacids (NBAA) with 10% of FCS on initial concentrations of I 2,0 to 3,0 x 10 4 cells/cmz with sub-culture twice a week. They were more resistant lines than the A-72, = however, less sensitive to the CCV, and on MDCK there was not formation of citopatic effect (CPE). Initial concentrations of 6,0 to 7,0 x 10 4 cells/cm' were the best for the CRFK culture on microplates, using L-15 4 media with 5% of FBS at 37°C without CO2 atmosphere. For the replication of CCV sample K-378-20 the Best conditions were using pH between 5,0 and 7,0, adsoption time of 90 minutes, with formation of 90% of CPE in three days in A-72 and five days in CRFK, obtainning the average of 10 5 DICC50/25ul of infectant titer with reading best time of 72 to 96 hours after inoculation. Through the use of immunodifusion technique in agar gel(IDAG) it was seen the presence of 29 seras (19%) positive for the CCV K-378-20 in samples of 157 canine seras collected in Belo Horizonte in period before the commercialization of the CCV vaccines in the Brasil.